2021
DOI: 10.3389/fnut.2021.777246
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Status of Children, Teenagers, and Adults From National Health and Nutrition Surveys in Mexico From 2006 to 2020

Abstract: Background: Population-level health and nutrition surveys provide critical anthropometric data used to monitor trends of the prevalence of under nutrition and overweight in children under 5 years old, and overweight and obesity in the population over 5 years of age.Objective: Analyze the children malnutrition and overweight and obesity in children, teenagers and adults through the National Health and Nutrition Surveys information available from public databases.Materials and Methods: Comparable anthropometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Notably, we observed that a decrease in overweight was reported throughout the survey years, at the expense of increases in obesity, where today these two outcomes show similar behavior. In Mexico, OW and OB together in the year 2006 showed a prevalence of 34.8%; in the year 2020 this rose to 38.2%, where prevalence of OW was 20.2 and 19.6%, respectively, and prevalence of OB was 14.6% and rose four percentage points ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we observed that a decrease in overweight was reported throughout the survey years, at the expense of increases in obesity, where today these two outcomes show similar behavior. In Mexico, OW and OB together in the year 2006 showed a prevalence of 34.8%; in the year 2020 this rose to 38.2%, where prevalence of OW was 20.2 and 19.6%, respectively, and prevalence of OB was 14.6% and rose four percentage points ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is thanks to the National Nutrition Surveys of 1988 and 1999 and the first National Nutrition and Health Survey (ENSANUT for its Spanish acronym) in 2006, which recorded significant increases in the prevalence of these conditions in women and children ( 1 ). In school-age children, the prevalence of overweight and obesity was 34.8% in 2006, 34.4% in 2012, 33.4% in 2016, 35.6% in 2018, 38.2% in 2020, and up to 37.3% in the year 2021 ( 2 – 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stunting (short height for age) and low birth weight, however, remain a problem (4.4.% prevalence of low weight and 15.5% prevalence of stunting in under 5-year-olds in 2020). 12 This is alongside a growing prevalence and health burden related to over-nutrition.…”
Section: Changing Power Dynamics Between Mexican Food Actors -Will Th...mentioning
confidence: 99%
“…Stunting (short height for age) and low birth weight, however, remain a problem (4.4.% prevalence of low weight and 15.5% prevalence of stunting in under 5-year-olds in 2020). 13 This is alongside a growing prevalence and health burden related to over-nutrition. Mexico has disproportionately high rates of obesity: 78.0% of the adults are either overweight or obese; and 8.4% of under 5-year-olds as well as 38.2% of school children are overweight.…”
Section: How Can the Mexican Political And Economic Context Facilitat...mentioning
confidence: 99%
See 1 more Smart Citation